Modulated Expression and Activities of Ruditapes philippinarum Enzymes After Oxidative Stress Induced by Aerial Exposure and Reimmersion - Nie, Hongtao; Jiang, Kunyin; Zhou, Zihan; Guo, Baiying; Li, Dongdong; Yan, Xiwu (Frontiers in Physiology, 2020)
Ruditapes philippinarum, is an economically and scientifically important bivalve mollusk. Its tolerance of aerial exposure has long been considered an important trait for its survival under acute environmental stress. In this study, the effects of air exposure at high and low temperatures (28 °C and 4 °C) on the survival, antioxidant and metabolic enzyme activities, and the expression of antioxidant and immune-related genes in R. philippinarum were investigated. The activities of antioxidant and metabolic enzymes (superoxide dismutase [SOD], α-amylase, and proline hydroxylase [PHD]) were significantly affected by aerial exposure and reimmersion (reoxygenation) at both low (4 °C) and high (28 °C) temperatures. Moreover, the mRNA expression of α-amylase, SOD, and C-type lectin was also examined, which reveals these genes were significantly affected by aerial exposure challenge. In addition, the effects of aerial exposure and reimmersion on survival rate were calculated to evaluate the recovery capacity of Manila clam after aerial exposure at high and low temperatures. All individuals survived under low temperature aerial exposure for 24 h and reimmersion for 120 h. However, individuals died after reimmersion for 12 h following high temperature aerial exposure, and mortality peak occurred at 48 h. These data indicate that long-term aerial exposure during the transportation of clams should be in a low temperature environment. This study demonstrates that enzyme expression and activities linked to the stress response increase during the aerial exposure of R. philippinarum and provide useful information for future work on the molecular basis of tolerance of aerial exposure stress.